Compassionate nursing in challenging contexts: The importance of judgments - Peter, Elizabeth (Nursing ethics, 2025)
BackgroundNurses’ demonstration of compassion is an ethical and often regulatory expectation. While research has been conducted to examine the barriers and facilitators of compassion in nurses, little is known about how nurses develop and express compassion for patients who may be blamed for their health condition. Unvaccinated COVID-19 patients are an example of such patients.Research questionsHow do nurses provide compassionate care for unvaccinated adults infected with COVID-19? How did the context of COVID-19 vaccination in Canada shape nurses’ relationships with unvaccinated patients?Research designA generic qualitative approach using interviews to gather data was used. Martha Nussbaum’s conceptualization of compassion and its cognitive requirements was employed to add depth to the analysis.Participants and research contextSeventeen Registered Nurses, from a range of practice settings, who had cared for unvaccinated patients with COVID-19 participated.Ethical considerationsEthics approval was received, and signed informed consent was obtained. Participants who were the current students of the researchers were excluded.FindingsThree themes were identified:1) Encountering Extreme Workplace Impediments to Compassion.2) Managing Emotions to Provide “Nonjudgmental Care.”3) Practicing Narrative Imagination.DiscussionThe difficult working conditions during the pandemic impeded nurses’ capacity to be compassionate. Yet, none judged their patients’ suffering as trivial, and all provided necessary nursing care. Some initially blamed these patients for the severity of their illness and suppressed their emotions to provide what they called “nonjudgmental care.” Upon reflection, participants recognized that these patients’ life circumstances may have been barriers to vaccination which, in the end, facilitated the development of compassion.ConclusionThis research has implications that go beyond that of caring for patients with COVID-19. The ideal of “nonjudgmental care” requires critical re-examination because judgments and emotions are required for compassion.